Relationship Between Central Obesity and The Risk of Hypertension in Obesity Adolescents - Ardina Maharani, Putri; Widjaja, Nur Aisiyah; Ardiana, Meity; Hanindita, Meta Herdiana (Asian Journal of Social and Humanities, 2023)
The increasing prevalence of central obesity in adolescents is accompanied by an increase in risk factors for cardiovascular disease. The study aims to analyze the relationship between central obesity and the risk of hypertension in obese adolescents, including both male and female subjects. This study was undertaken to provide opportunities for further exploration of the relationship between central obesity and hypertension in adolescents. The study was a retrospective observational study that utilized medical record data from a previous research project entitled "Polimorfisme Gen Adiponectin ADIPOQ +45 T>G, ADIPOQ – 11377 C>G dengan Kadar Adiponektin Pada Remaja Obesitas dan Resiko Sindrom Metabolik." This data was obtained from research conducted on obese adolescents aged 13-18 years in junior and senior high schools in Surabaya and Sidoarjo who met the criteria. The sample comprised 140 obese adolescents, who were then categorized into two groups: those without central obesity and those with central obesity. Statistical data were analyzed using SPSS with the Chi Square test. There is a very strong and significant relationship between central obesity and the risk of hypertension in obese adolescents (p = 0.000; r = 0.373); central obesity and the risk of hypertension in obese male adolescents (p = 0.001; r = 0.587); and central obesity and the risk of hypertension in obese female adolescents (p = 0.003; r = 0.300). The study found a significant relationship between central obesity and hypertension risk in obese adolescents. Adolescents with central obesity were 3.6 times more likely to develop hypertension than those without. Male adolescents with central obesity were 6.5 times more likely to develop hypertension than those without. Female adolescents with central obesity were 2.9 times more likely to develop hypertension